EFFECTS OF PAPAVERINE AND SODIUM NITROPRUSSIDE SOLUTION AS TOPICAL VASODILATORS FOR INTERNAL MAMMARY ARTERY - Chaudhry,, mtiaz Ahmed (Pakistan Armed Forces Medical Journal, 2011)
Objective: To compare the effects of topical sodium nitroprusside (SNP) and papaverine solutions to treat left internal mammary artery spasm. Study Design: Randomized Control Trial (RCT). Place and duration of Study: AFIC / NIHD Rawalpindi from Jan 2009 to March 2009. Patients and Methods: Fifty consecutive patients undergoing elective coronary artery bypass graft surgery (CABG) were randomly assigned to two groups: group N (n=25, Sodium Nitroprusside solution), and group P (n=25, Papaverine). In each patient, pedicled left internal mammary artery was harvested, five minutes after heparin administration, left internal mammary artery was divided distally; flow per minute was calculated after measuring the free flow for over 15 seconds; this is named “Flow 1.” Then, the pedicled left internal mammary artery was sprayed with the randomized solution, and covered with the test solution soaked sponge. The second flow measurement “Flow 2” was done before commencing cardiopulmonary bypass. A third flow measurement “Flow 3” was recorded just before left internal mammary artery to left anterior descending coronary artery anastomosis, while the patient was on cardio pulmonary bypass. Results: Analysis of variance was applied to detect differences among groups; paired-sample t test was used for left internal mammary artery topical free flow in both groups. Mean left internal mammary artery free flows were as follows: group N, flow1=32.72±27.67 ml/min, versus group P flow1=23.44±15.16 ml/min (p<0.148), group N flow2=63.92±33.40 ml/min versus group P flow2=38.88±24.54 ml/min (p<0.004), and group N flow3=62.44±38.38 ml/min versus group P flow3=49.52±30.29 ml/min (p <.170). Topical free flow difference amongst the two groups was statistically significant in the flow2 (p< 0.004); whereas topical mean free flow difference was statistically significant when the groups were individually compared group N flow1:flow2, flow 1: flow 3and flow 2: flow 3 group N (p<.000, .000, .846) and group P (p<.001, .000, .001) respectively. Conclusion: Sodium nitroprusside (SNP) and papaverine solutions are able to treat vascular spasm and increase the flow of left internal mammary artery, when they are used topically. However sodium nitroprusside allows early and better relief of vascular spasm.